Acquiring constraints on morphosyntactic variation: children's Spanish subject pronoun expression - SHIN, NAOMI LAPIDUS (Journal of child language, 2016)
Constraints on linguistic variation are consistent across adult speakers, yielding probabilistic and systematic patterns. Yet, little is known about the development of such patterns during childhood. This study investigates Spanish subject pronoun expression in naturalistic data from 154 monolingual children in Mexico, divided into four age groups: 6–7, 8–9, 10–11, 12+. Results from logistic regressions examining five predictors of pronoun expression in 6,481 verbs show that children's usage is structured and patterned. The study also suggests a developmental progression: as children get older, they become sensitive to more constraints. I conclude by suggesting that children learn patterns of variation by attuning to distributional tendencies in the input, and that the more frequent the patterns are, the easier they are to detect and learn.